2002
DOI: 10.1002/rnc.675
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of linear parameter‐varying systems using a non‐smooth dissipative systems framework

Abstract: SUMMARYThis paper presents new finite-dimensional linear matrix inequality formulations for several important analysis problems of linear parameter-varying systems. The approach is based on a non-smooth dissipative systems framework using a continuous, piecewise-affine parameter-dependent Lyapunov function. The new analysis approach yields guaranteed and less conservative results than previously published techniques that are based on affine parameter-dependent Lyapunov functions or Lur! e e-Postnikov Lyapunov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Note that the parameter µ is generally piecewise smooth and, thus, is different from the counterpart of SLPV systems. 3 However, Lim and Chan 4 recently showed that this difference has no effect on the SLPV analysis and synthesis. Also, note that each A i .µ/ is an af ne matrix function of µ (Ref.…”
Section: Quaternion Controller Designmentioning
confidence: 98%
See 3 more Smart Citations
“…Note that the parameter µ is generally piecewise smooth and, thus, is different from the counterpart of SLPV systems. 3 However, Lim and Chan 4 recently showed that this difference has no effect on the SLPV analysis and synthesis. Also, note that each A i .µ/ is an af ne matrix function of µ (Ref.…”
Section: Quaternion Controller Designmentioning
confidence: 98%
“…3 First, Eq. (2) is conservatively modeled into a quasi-SLPV system with three assumptions: 1) the x of A.x/ is the parameter µ that is independentof the state x, 2) the unit-normquaternion constraint is ignored (which implies ¡1 · q k D 1;:::;4 · 1), and 3) the angular velocity !…”
Section: Quaternion Controller Designmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, a coarse application of the Lyapunov-based synthesis techniques available for linear systems is impossible, as it leads to solve an infinite number of linear matrix inequalities (LMIs). At this poinf two types of methods are usually used (see the recent works [8], [6] on LPV systems):…”
Section: Introductionmentioning
confidence: 99%